Call for urgent actions to ensure access to early diagnosis and care of tuberculosis among refugees: Statement of the European Respiratory Society and the European Region of the International Union Against Tuberculosis and Lung Disease. Issue 5 (24th March 2016) - Dara, Masoud; Solovic, Ivan; Sotgiu, Giovanni; D'Ambrosio, Lia; Centis, Rosella; Goletti, Delia; Duarte, Raquel; Aliberti, Stefano; de Benedictis, Fernando Maria; Bothamley, Graham; Schaberg, Tom; Abubakar, Ibrahim; et al.
Tuberculosis (TB) is a major cause of mortality from an infectious disease, globally affecting 9.6 million cases, with 1.5 million deaths in 2014 [1]. In 2014, there were 273 381 TB cases reported in the World Health Organization (WHO) European region, and an estimated 33 000 deaths [2]. Vulnerable populations ( i.e . individuals affected by discrimination, hostility or economic adversity), which often include migrants and refugees, have an increased risk of suffering from TB disease [1, 3, 4]. If this is not efficiently addressed, the exposure of these groups to Mycobacterium tuberculosis strains may lead to a rise in the number of cases of disease and related deaths, as well as contributing to a further increase in drug-resistant TB cases. ERS and the European Region of The Union call for prioritisation of TB care, prevention and control among refugees http://ow.ly/YYCL8